Clinical Practice, Challenges, and the Future of Ophthalmic Genetics in Saudi Arabia - AlMoallem, Basamat; Alsuwailem, Ghadah; Alqahtani, Nadeef; Alshammari, Layan; Alkhodier, Abeer (Journal of Ophthalmic and Vision Research, 2025)
Purpose: Ophthalmic genetics is vital for diagnosing and managing inherited eye disorders, contributing to personalized treatments. Methods: This cross-sectional study assessed 131 healthcare professionals in Saudi Arabia through an online questionnaire to evaluate clinical practices, referral patterns, and challenges in genetic ophthalmology. Results: Our study showed that 61.7% of participants reported the availability of ophthalmic genetics services in their hospitals, with an equal percentage referring patients to genetic specialists. However, significant barriers were identified, including limited budgets for genetic testing (69.6%), a lack of trained physicians (70.9%), low community awareness (50.6%), and a perceived lack of treatment options (27.8%). Additionally, concerns about patient access to genetic testing (54.3%) and genetic counseling (50.6%) were highlighted. Conclusion: This is the first study on ophthalmic genetics in Saudi Arabia, and its findings emphasize the need for policy reforms and targeted interventions. Proposed solutions include innovative financial models for genetic testing, expanded training programs for healthcare providers, and public awareness campaigns to improve access to genetic services. Addressing these challenges can enhance early diagnosis, treatment strategies, and patient outcomes in ophthalmic genetics.